Islam and Western Debates on Human Rights - Yumitro, Gonda (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2015)
Eventhough there are overlapping and intersection in defining the concept of Human Rights, Islam and Western have serious debates on it. The debates started from the different sources of human rights. Islam put the revelation as the foundation of its rule and Western mostly depend on the individual freedom. In term of its implementation, Western critizes Islam as the ideology as well as actor behind the violation of human rights. In its point of views, Islam distinguishes the rights of the people based on the concepts of Islamic state, gender inequality, and various kinds of inhumane shariah law. On the other hand, Islam argues that Islam has more complete and advance concept of human rights than the Western since Western does not concern on the social rights of people. Even if the concept is analyzed based on the Islamic values and history, it would be clear that Islam promote human rights seriously. For some of controversial issues in Islamic shariah such as qishos, amputation and inheritance, Islam assures that they have many benefits for the common rights of the people.